THE EFFECT OF SERVICE QUALITY AND PRICE PERCEPTION ON REVISIT INTENTION MEDIATED BY TRUST AT PRIMAYA HOSPITAL BETANG PAMBELUM PALANGKARAYA - Asty Selevani; Eka Desy Purnama; Fushen (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to analyze the effect of service quality and price perception on revisit intention, with trust as a mediating variable, on health check-up (MCU) patients at Primaya Betang Pambelum Hospital, Palangkaraya. This study is motivated by the importance of understanding the factors that influence patient loyalty in health services. The study used a quantitative approach with the Structural Equation Modeling Partial Least Square (SEM-PLS) method. Data were collected through questionnaires distributed to patients who had used MCU services. The variables studied included service quality, price perception, trust, and revisit intention. The results showed that service quality had a significant positive effect on trust (β = 0.550; p = 0.000) and revisit intention (β = 0.313; p = 0.002). Likewise, price perception had a positive effect on trust (β = 0.357; p = 0.000) and revisit intention (β = 0.240; p = 0.003). Trust itself has been proven to have a significant effect on revisit intention (β = 0.334; p = 0.010). In addition, trust significantly mediates the relationship between service quality and price perception on revisit intention. In conclusion, service quality and price perception affect patient revisit intention both directly and indirectly through trust. Therefore, improving service quality and price affordability are key strategies to strengthen patient loyalty to hospital health services.